Jorgos Viziinos, Chi fu l’assassino di mio fratello, edición de Vincenzo Rotolo, L’epos, Palermo, 2000, ISBN 88-8302-139-8 (Minerva, 2019)
Review: Jorgos Viziinos, Chi fu l’assassino di mio fratello, edición de Vincenzo Rotolo, L’epos, Palermo, 2000, ISBN 88-8302-139-8